Large-scale reduction of the Bacillus subtilis genome: consequences for the transcriptional network, resource allocation, and metabolism - Reuß, Daniel R.; Altenbuchner, Josef; Mäder, Ulrike; Rath, Hermann; Ischebeck, Till; Sappa, Praveen Kumar; Thürmer, Andrea; Guérin, Cyprien; Nicolas, Pierre; Steil, Leif; Zhu, Bingyao; Feussner, Ivo; et al. (Genome research, 2017)
Understanding cellular life requires a comprehensive knowledge of the essential cellular functions, the components involved, and their interactions. Minimized genomes are an important tool to gain this knowledge. We have constructed strains of the model bacterium, Bacillus subtilis , whose genomes have been reduced by ∼36%. These strains are fully viable, and their growth rates in complex medium are comparable to those of wild type strains. An in-depth multi-omics analysis of the genome reduced strains revealed how the deletions affect the transcription regulatory network of the cell, translation resource allocation, and metabolism. A comparison of gene counts and resource allocation demonstrates drastic differences in the two parameters, with 50% of the genes using as little as 10% of translation capacity, whereas the 6% essential genes require 57% of the translation resources. Taken together, the results are a valuable resource on gene dispensability in B. subtilis , and they suggest the roads to further genome reduction to approach the final aim of a minimal cell in which all functions are understood.